Exolytic products of alginate by the immobilized alginate lyase confer antioxidant and antiapoptotic bioactivities in human umbilical vein endothelial cells. (1st January 2021) - Jiang, Zedong; Zhang, Xiwen; Wu, Liyang; Li, Hebin; Chen, Yanhong; Li, Lijun; Ni, Hui; Li, Qingbiao; Zhu, Yanbing
Highlights: Alginate lyase is covalently immobilized on Fe3 O4 nanoparticles. Stability and moderate reusability of immobilized alginate lyase are enhanced. Immobilized alginate lyase efficiently produces alginate oligosaccharides. Alginate oligosaccharides show potent antioxidant effect in H2 O2 -stressed HUVECs. Alginate oligosaccharides inhibit apoptosis in H2 O2 -stressed HUVECs. Abstract: Alginate is a natural polysaccharide resource abundant in brown algae and it can be cleaved into alginate oligosaccharides by alginate lyase. Alginate lyases and the bioactive alginate oligosaccharides have been applied in diverse fields such as pharmaceutical therapy and nutraceutical supplementation. Immobilized enzymes greatly facilitate their industrial application owing to their reusability, stability, and tunability. In this study, magnetic Fe3 O4 nanoparticles were synthesized and used to immobilize an exolytic alginate lyase AlgL17 that was characterized previously. The immobilized AlgL17 demonstrated enhanced thermal and pH tolerance, extended storage stability, and moderate reusability. The mass spectrum indicated the specific activity of the immobilized AlgL17 to release alginate oligosaccharides (AOS) from alginate polysaccharide. The produced AOS exhibited their antioxidant and antiapoptotic activities in H2 O2 -stressed human umbilical vein endothelial cells by upregulation of reactive oxygen species scavenging activities and attenuation of the caspase-mediated apoptosis pathway.